Anaerobic Digestion and Composting as Methods of Bio-Waste Management (Agricultural Engineering, 2023)
The management of biodegradable waste from various sectors of economy is an essential element in terms of environmental protection. The paper discusses issues related to the possibility of bio-waste treatment using anaerobic digestion technologies and composting processes, highlighting the conditions for the processes and their advantages and disadvantages. The challenges of overproduction of bio-waste faced by highly developed countries around the world are also presented. Research showed that the anaerobic digestion of this waste combines both biofuel production and a circular economy. The popularity of this method is linked, among others to a low cost of raw materials and wide range of possible uses for biogas (i.e. electricity, heat, or biomethane). In addition, an alternative bio-waste management option, compost production, was discussed. The study aimed to compare anaerobic and aerobic bio-waste management processes.